2009
DOI: 10.1007/s10453-008-9108-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the patulin-producing potential of some Paecilomyces variotii strains isolated from the air samples of Jeddah City, Saudi Arabia, using the RAPD-PCR technique

Abstract: Random amplified polymorphic DNA polymerase chain reaction (RAPD-PCR) analysis was used to detect the patulin-producing potential among seven different strains of Paecilomyces variotii isolated from air samples collected in Jeddah City, Saudi Arabia. Using five different primers, the strains showed some similarities and distinct RAPD patterns. A correlation between isolation source and clustering was noted in the constructed dendrogram. Patulin-producing strains showed identical RAPD patterns. Primer M13 produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Other studies indicated no relationship between RAPD profi les and severity of toxicity (35)(36)(37). In contrast, identical RAPD patterns were demonstrated in patulinproducing Paecilomyces variotii strains (38), ochratoxin A-producing Aspergillus species (39), and aflatoxins-producing A. flavus strains (40). We concluded that RAPD analysis can be used in the intraspecifi c differentiation of toxigenic P. citrinum strains obtained from air samples.…”
Section: Discussionmentioning
confidence: 70%
“…Other studies indicated no relationship between RAPD profi les and severity of toxicity (35)(36)(37). In contrast, identical RAPD patterns were demonstrated in patulinproducing Paecilomyces variotii strains (38), ochratoxin A-producing Aspergillus species (39), and aflatoxins-producing A. flavus strains (40). We concluded that RAPD analysis can be used in the intraspecifi c differentiation of toxigenic P. citrinum strains obtained from air samples.…”
Section: Discussionmentioning
confidence: 70%
“…The ability of different species of the genus Paecilomyces to produce mycotoxin and other biological metabolites has been reported in previous studies [ 9 ]. According to Bokhari et al [ 41 ], P. variotii produces the genotoxic mycotoxin, patulin. Peptide mycotoxins known as leucinostatins, with activity against fungi, are extracted from P. lilacinus and possess high toxicity to experimental animals [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Random amplified polymorphic DNA polymerase chain reaction (RAPD-PCR) analysis was used to detect PAT-producing potential among seven different strains of Paecilomyces variotii isolated from air samples collected in Jeddah City, Saudi Arabia. In conclusion, this study has shown that there is considerable genotypic variability among the strains of P. variotii and it may be possible to construct a specific primer set for detecting PAT-producing strains (Bokhari et al, 2009). Bandoh et al (2009) inoculated spores from Aspergillus and Penicillium species into apples and following incubation examined the subsequent distribution of PAT contamination in the apple.…”
Section: Patulinmentioning
confidence: 93%